WHY HAS STATE V. HUTCHINSON BEEN IGNORED? AN ANALYSIS OF WHY UTAH CITIES LACK AUTHORITY TO EXACT WATER (Utah Environmental Law Review; Vol 28 No 2 (2008))
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The wisdom of Will Rogers is invoked for the proposition that, in the West, whiskey is for drinking and water is for fighting over. “Although overall water consumption is not increasing significantly in the United States, the demand for water in certain sectors is rapidly growing. ”   Specifically, demand for water in the West has always been high due to the arid landscape and drought cycles. “The West,” as understood in the context of water use and management is typically identified as the seventeen coterminous states located west of the Hundredth Meridian and exclusive of California, Oregon, and Washington. The Hundredth Meridian is used because precipitation rates east of that boundary average forty inches or more per year, while rates west average less than twenty inches. Oregon, Washington, and California are excluded because of their relationship with the Pacific Ocean which creates rainfall in excess of 100 inches in certain areas within those states.